A Complete Denture Impression Technique Survey of Postdoctoral Prosthodontic Programs in the United States. Issue 4 (7th October 2013) - Mehra, Mamta; Vahidi, Farhad; Berg, Robert W.
Abstract Purpose The purpose of the study was to survey program directors of postdoctoral prosthodontic programs in the United States regarding their programs' complete denture impression techniques. The key objectives of the survey were to identify the current trends in complete denture impression making and to determine which techniques and materials are taught in US postdoctoral prosthodontic programs. Materials and Methods An online survey was sent to all program directors of US postdoctoral prosthodontic programs. The survey comprised two sections: preliminary impressions and final impressions. The survey contained 22 questions that would take approximately 5 minutes to complete. All responses remained anonymous throughout the survey. Results The response rate for the survey was 87%. A majority of the programs did not separately border mold the tray prior to making the preliminary impressions (82%). The impression material of choice for the preliminary impression was irreversible hydrocolloid (88%). Selective pressure was the predominantly used impression philosophy (80%). All programs border molded the custom tray, and 95% recorded the borders in sections. The material of choice for border molding the custom tray was modeling plastic impression compound (71%). The most commonly used impression material for the final impressions was polyvinylsiloxane (PVS) (42%), and the second most commonly used impression material was polysulphide (32%). The most common technique for locating the posterior palatal seal was marking intraorally and transferring onto the final impression (65%). Most programs routinely advised their patients not to wear their existing dentures for at least 24 hours before the final impressions were made (83%). Conclusions Based on the results of this study, the following conclusions can be drawn: (1) The most commonly used material for the preliminary impression was irreversible hydrocolloid and for the final impression was PVS. (2) Modeling plastic impression compound was used by most programs to border mold the custom trays. (3) Selective pressure was the predominantly used impression philosophy. (4) A majority of the programs made a special consideration for excessive movable (flabby) tissue. (5) Most programs routinely advised their patients to not wear their existing dentures for at least 24 hours before the final impressions were made.